Penerapan Algoritma C4.5 Untuk Kepuasan Pelanggan Toko Online Parfume Chantik - Aditya Nugroho, Caesar Rizky; Kristiana, Titin (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2022)
Currently, there are many online stores or marketplaces either owned by individuals / companies that are specifically eduated by buyers or costumers who want to see and buy products. In some countries in the world, the marketplace functioned as electronic commerce is often interpreted as e-commerce in several locations in Indonesia. The difference between marketplace and e-commerce is in a concept similar to the traditional market / store. In this study used the C4.5 Algorithm method to analyze the quality of service satisfaction and products from online stores perfume chantik. Using the C4.5 algorithm method, it is necessary to know the accuracy of predictions, namely the ability of models to be able to predict class labels against new data or previously unknown data well. In this study, experiments were conducted using the C4.5 algorithm's data mining deceision tree classification method against customer satisfaction kuisoner data after buying from an online store parfume chantik.